Organic and natural cosmetic products : How safe are they? - Vasiljević Dragana; Bojović Lidija (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2018)
There is a growing demand for organic and natural cosmetic products, especially in the EU countries and the rest of the world, as the consumer awareness for the preservation of the environment and natural resources has increased, but above all with the belief that these products are safe. All cosmetic products, even organic and natural, that are placed on the market of EU countries must comply with the Cosmetics Regulation 1223/2009 EC requirements in terms of quality, safety and efficacy. However, there is no harmonized European regulation today, that sets out the criteria for natural and organic cosmetic products. The most important standards for natural and organic cosmetics in the EU countries are COSMOS and NATRUE standard. According to the requirements of these standards, selected raw materials, mainly of plant origin, which are processed by approved procedures, are allowed for organic and natural cosmetic products manufacturing. Numerous studies indicate that toxicological properties of natural substances deserve much more attention, in order to determine their safety. The safety, efficacy and quality of cosmetic products are prerequisites. That is why it is necessary to create a regulatory framework for natural and organic cosmetic products, which will not mislead the consumers and which will be more binding for manufacturers. Also, it is necessary to create a precise guideline for the safety assessment of organic and natural cosmetic products.